Association of Prosthodontic Diagnostic Index (PDI) in Establishing Proper Treatment for Partial Edentulism and Completely Dentate Patients - Javaheri, Mohammad Reza; Dzodzuashvili, Grigol (Caucasus Journal of Health Sciences and Public Health, 2020)
The indices are developed for use in the diagnosis and treatment of partially edentulous and completely dentate patients by dental professionals. Advantages of the program include improved intraoperator consistency, enhanced professional communication, coverage of premiums commensurate with difficulty of treatment, improved screening method for dental school admission clinics, standardized outcome evaluation and testing standards, improved diagnostic consistency, and streamlined assistance in the decision to refer a patient. For the partially edentulous, each class (ideal or minimal, moderately compromised, substantially compromised, or severely compromised) has the following specific diagnostic criteria: Location and extent of the edentulous area or areas, Condition of the abutment teeth, Occlusal scheme, Residual ridge. Only tooth condition and occlusal scheme are assessed in completely dentate patient.